1942
DOI: 10.1021/ja01256a504
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Ytterbium from Accompanying Rare Earths by Means of its Amalgam

Abstract: NOTES 1009rigorous purification the m. p. can be raised to 88-89'. On catalytic hydrogenation the alcohol absorbs 0.9-1.0 mole of hydrogen.' Three grams of a non-alcoholic liquid were recovered from the volatile fraction obtained during the above ethyl borate treatment. The substance polymerized very rapidly on heating and this property, together with the rotation, refractive index, and method of preparation, indicates that it was probably impure carvopinone.8 (6) Jbshel, Hall and Palkin, I n d . Eng. Chcm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1945
1945
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, by electrolytic reduction at a mercury cathode in alkaline acetate solutions containing potassium citrate and potassium carbonate, McCoy (5,6) prepared europium, ytterbium, and samarium amalgams in yields decreasing in this order. By this method, europium was readily removed from rare earth mixtures (6) and ytterbium was extracted with somewhat less efficiency (7). While McCoy was unable to obtain amalgams of the other rare earth elements by this procedure, he did obtain europium, ytterbium, and samarium amalgams by treating acetate solutions containing citrate and potassium carbonate with potassium amalgam (5,6).…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by electrolytic reduction at a mercury cathode in alkaline acetate solutions containing potassium citrate and potassium carbonate, McCoy (5,6) prepared europium, ytterbium, and samarium amalgams in yields decreasing in this order. By this method, europium was readily removed from rare earth mixtures (6) and ytterbium was extracted with somewhat less efficiency (7). While McCoy was unable to obtain amalgams of the other rare earth elements by this procedure, he did obtain europium, ytterbium, and samarium amalgams by treating acetate solutions containing citrate and potassium carbonate with potassium amalgam (5,6).…”
Section: Acknowledgmentmentioning
confidence: 99%
“…The nitrate was excluded because previous experiments had shown that nitrate solutions, or even acetate solutions containing nitrate, yield no ytterbium amalgam when treated with sodium amalgam, probably because of preferential reduction of the nitrate. In addition, alkaline citrate solutions were studied to afford a comparison of the procedure with that of McCoy (5, 6, 7).…”
Section: Extraction Of Ytterbium From Solutions Containing Various An...mentioning
confidence: 99%